Pemberdayaan Masyarakat melalui Pengembangan Budi Daya Ikan Lele di Desa Balongan, Indramayu, Jawa Barat - Aris Darmansah; . Sulistiono; Thomas Nugroho; Eddy Supriyono (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Balongan Village is one of coastal area in Indramayu which is potential for aquaculture development. Community development through catfish culture activity in this village had been done for 3 years from December 2011-December 2014. This activity aimed to improve the community skill especially catfish culture using plactic pond. Methods used in this activity was training and empowering. The community was trained about plastic pond construction and fish culture technique. The community participated in first year was 21 people, second year was 26 people, and third year was 13 people. Supporting scheme in this program was one pond sized 5 x 5 m2 for one person, including fish larvae (seed) and feed for twice harvesting. There were two principal approaches had been done to empower the catfish culture activity which were technical and participative approach. The success of catfish culture program could be seen from three aspects namely participation, community income, and social modal utilization. Based on the training and empowering results, community had ability to culture and harvest the catfish reared in the plastic pond.